EVALUASI PROGRAM DALKARHUTLA UNTUK MENEKAN KEBAKARAN HUTAN DAN LAHAN DI UPT KPHP KOTAWARINGIN BARAT - Purnawan, Eldy Indra; Chotimah, Husnul; Effendi, Heri Rusli; Delmi, Anwari; Jemi, Renhart (Jurnal Hutan Tropis, 2025)
This study is an evaluation of the implementation of the Dalkarhutla Program to be an input in planning, strategy innovation, policy making and implementation of future activities in the UPT KPHP Kotawaringin Barat management area. This study was conducted using quantitative methods using descriptive analysis by collecting secondary data on the achievements of the UPT KPHP Kotawaringin Barat Dalkarhutla Program in 2023, namely Dalkarhutla Patrol and Fire Extinguishing. The results of the study showed that the intensity of Dalkarhutla Patrols was carried out in six sub-districts in the UPT KPHP Kotawaringin Barat management area and the highest intensity of Dalkarhutla Patrols was in Arut Selatan District (32%), Kumai District (29%) and Kotawaringin Lama District (18%). There are four findings of the Dalkarhutla Patrol, namely locations prone to burning, not found locations prone to burning, locations of burn marks and water sources. Meanwhile, Fire and Fire Extinguishing focused on Kumai District with 18 blackouts and Arut Selatan District with 6 blackouts. West Kotawaringin District hotspot data is dominated by Arut Selatan District (772 hotspots) and Kumai District (6,714 hotspots). These results show that Dalkarhutla Patrols in the UPT KPHP Kotawaringin Barat Management Area need to continue, preparedness in carrying out forest and land fire suppression, especially in Kumai District and  Arut Selatan District, and strategy innovation is needed in an effort to prevent forest and land fire incidents in the West Kotawaringin KPHP UPT management area.